Affective Reeducation and Access to Resources: An Intervention Model for Older Women Victims of Gender-Based Violence - Hurtado, Sol (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2026)
Gender-based violence against older women has historically been rendered invisible within intervention frameworks and public policies. Despite having experienced prolonged periods of violence, these women are often left out of institutional focus due to both structural factors and social representations that view them as detached from desire, affectivity, or the capacity for change. The weight of traditional gender mandates, and especially of romantic love myths, acts as a deep barrier to recognizing violence and making decisions that involve breaking with learned relational models. This article offers a critical analysis of current intervention models, particularly in relation to protection plans and recovery timelines. Drawing on both theoretical and practical perspectives, it proposes an alternative model focused on group support, affective educational intervention, and the need to rethink protection processes from a more comprehensive, flexible, and context-sensitive approach tailored to the realities of older women.